Identification of A Novel Picorna-Like Virus, Burpengary Virus, that is Negatively Associated with Chlamydial Disease in the Koala - Harvey, Erin (Viruses, 2019)
Koalas (Phascolarctos cinereus) are native Australian marsupials whose populations are in decline from a range of threats. Infectious diseases caused by the bacterium Chlamydia pecorum and other pathogens are of particular concern. We analysed 26 poly-A selected RNA-sequencing libraries from a data set designed to study the immune response of koalas to ocular chlamydial infection. Using virus discovery techniques, we identified the coding-complete genome sequence of a novel picorna-like virus, denoted Burpengary virus, that was most common in south-east Queensland. Notably, abundance measurements of the virus across all 26 libraries revealed an inverse relationship between abundance and ocular disease in koalas, suggesting that the co-infection of Burpengary virus and Chlamydia pecorum is inhibited.